Dakwah Melalui Tradisi Brokohan Masyarakat Jawa di Desa Rasau Jaya - ROMADHON, KHOIRUMAN AZKA (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2024)
Abstract:The Brokohan tradition is one of the traditions of Indonesian society, especially from the Javanese tribe which aims to expect barokahan from Allah SWT, for the blessings that have been given, namely in the form of offspring. The Brokohan tradition has been proven to be able to preserve the culture of gratitude, harmony and friendship of the Javanese people. This success is inseparable from the meanings and ways of the Javanese people in carrying out the brokohan tradition. This article tries to explain the meaning contained in barokohan as an effort to preserve the positive traditions of the Javanese people. The purpose of this study is for the general public to know about the meaning of the Brokohan tradition. The data collection process is carried out by qualitative methods, while the analysis uses descriptive analysis. The results of the analysis gave rise to 3 major themes regarding the meaning of the Brokohan tradition, namely: the meaning of gratitude to the creator, the meaning of friendship, and the meaning of harmony. The study of these three meanings is very useful for the general public, especially those who are in the Javanese tribal environment. The need for positive traditional data in the current era is important to be fulfilled immediately, in the midst of a pluralistic society and tribal conflicts caused by differences in traditions. The central theme in this article is the importance of preserving positive traditions in the midst of the onslaught of globalization.Keywords: Tradition, Brokohan, Javanese, Gratitude, Gathering, Harmony. Globalization.Abstrak :Tradisi Brokohan adalah salah satu tradisi masyarakat Indonesia, khusunya dari suku Jawa yang bertujuan untuk mengharapkan kebarokahan dari Allah SWT, atas nikmat yang telah diberikan yakni berupa keturunan. Tradisi Brokohan terbukti dapat melestarikan budaya syukur, kerukunan dan sillaturahim Masyarakat Jawa,. Keberhasilan itu tidak terlepas dari makna-makna dan cara masyarakat jawa dalam melaksanakan tradisi brokohan. Artikel ini mencoba memaparkan tentang makna yang terkandung dalam barokohan sebagai upaya pelestarian tradisi positif masyarakat Jawa. Tujuan Studi ini adalah supaya masyarakat umum mengenal tentang sebuah makna dari tradisi Brokohan. Proses pengumpulan data dilakukan dengan metode kualitatif, sedangkan untuk analisisnya menggunakan analisis deksriptif. Hasil analisis memunculkan 3 tema besar mengenai makna tradisi Brokohan yakni: makna syukur kepada sang pecipta, makna silaturahmi, dan makna kerukunan. Kajian tentang ketiga makna itu sangat berguna bagi khususnya masyarakat umum yang berada dalam lingkungan suku Jawa. Kebutuhan akan data tradisi yang positif di era saat ini, menjadi penting untuk segera dipenuhi, ditengah tengah masyarakat yang majemuk dan konflik-konflik kesukuan yang diakibatkan oleh perbedaan tradisi. Tema sentral dalam artikel ini adalah pentingnya melestarikan tradisi positif di tengah gempuran globalisasi.Kata-kata Kunci: Tradisi, Brokohan, Suku Jawa, Syukur, Silaturahmi, Kerukunan. Globalisasi.